Encountering patients with anorexia nervosa - An emotional roller coaster. nurses’ lived experiences of encounters in psychiatric inpatient care - Josefine Davén; Ove Hellzen; Marie Häggström (International Journal of Qualitative Studies on Health & Well-Being, 2022)
Purpose The aim of this study was to illuminate the meaning of nurses’ lived experiences of encounters with adult patients with anorexia nervosa in psychiatric inpatient care. Methods A qualitative phenomenological hermeneutical design was used. Personal interviews with a narrative approach were conducted with 11 nurses with experience of encountering patients with anorexia nervosa in psychiatric inpatient care. Results Three key themes were revealed: Being overwhelmed by emotions consisting of three subthemes: Bearing feelings of incomprehension, Navigating emotions, and Being disappointed and frustrated; Seeking strength to cope consisting of three subthemes: Relying on colleagues and routines, Feeling hope and motivation, and Building inner security; and Trying to build relations consisting of two subthemes: Getting closer to the patient and Relating to relatives. Conclusion Our findings illuminate the “emotional roller-coaster” which nurses are embedded in during their daily work experiences. Being able to balance one’s professional role, seeing the person behind the patient, and the illness is important in all nurse-patient encounters. An examination of nurses’ lived experiences can contribute new and important knowledge, an in-depth understanding of the nurses’ work situation, and can help identify any need for increased knowledge.